Advances in the removal of emerging contaminants from water mediated by chemically modified biochar - LI Xiting; DONG Haoran* (能源环境保护)
Emerging contaminants are pollutants with relatively low concentration but high toxicity. They can be enriched in living organisms and transferred to the human body through the food chain, posing a significant threat to environmental ecology and human health. Additionally, the harm caused by emerging contaminants in the environment is latent, hidden and persistent. Therefore, it is of great practical significance to choose appropriate methods to control the risk of emerging contaminants. In the context of "double carbon action" , biochar adsorption for emerging contaminants removal has aroused extensive research interest. However, it should be noted that the original biochar has limitations in many applications, such as weak adsorption capacity, poor selectivity, and low chemical stability. Therefore, it is necessary to modify biochar to improve its application in water treatment. Currently, chemical modification of biochar is the most widely used method of modification. This paper introduces three commonly used chemical modification methods of biochar: acid modification, alkali modification and metal salt/oxide modification. The mechanisms by which these methods enhance the physical and chemical properties of biochar are also discussed. Furthermore, the synergistic mechanism of chemically modified biochar mediated removal of emerging contaminants is analyzed, primarily involving adsorption and advanced oxidation processes. The research progress of chemically modified biochar in the removal of typical emerging contaminants such as PPCPs, EDCs, PFCs and MPs in the past five years is summarized. Finally, this paper proposes future research directions for the chemically modified biochar mediated removal of emerging contaminants to provide a reference for the green and efficient removal of emerging contaminants from water.